A Critical Analysis of the Human Assisted Reproductive Technology Bill, 2023 - Maria Mirembe Aliba (Uganda Christian University, 2024)
This study is about Assisted Reproductive Technology, a cure for both primary and secondary infertility. Uganda has no law that provides for ART however a bill was brought by Hon.Sarah Opendi to provide got a legal framework for ART. The author in this thesis, critically anayzed the Human Assisted Reproductive Technology Bill, 2023 from a human rights perspective.